Does the world belong to the smart ones? Dishonest behavior in business schools - Abelha, Daniel Martins; Falcão, Roberto Pessoa De Queiroz; Perpétuo, Cristiane Koda; Vilela, Nágila Giovanna Silva; Miyazaki, Fernando Rejani (Revista de Administração da UFSM, 2023)
Purpose: the main objective of this study is to analyze the meanings and perceptions of graduate program students (master's and doctoral students) in Business Administration, as well as professors of graduate programs (PPGs) from different institutions, in relation to possible practices of dishonest behavior and plagiarism in the academic context. It highlights the causes, consequences and meanings of possible practices of dishonest behavior and plagiarism in the academic context, using the theoretical framework of possible reasons for plagiarism and dishonest behavior in this context. Design/methodology/approach: the perceptions of 28 professors and students were analyzed, extracted from semi-structured interviews and questionnaires, and later analyzed using Flores' categorical analysis, where the qualitative data were reduced, categorized, and coded, capturing the relevant meanings. Findings: the study highlights the phenomenon of academic dishonesty through reports from professors and students, listing four metacategories: meaning and perception of the phenomenon, causes, consequences and forms of combat, which in turn generated seven other categories. Practical implications: possible causes and implications of plagiarism are discussed, as well as ways to combat or mitigate the impact of these acts in Business Administration teaching programs, fostering the debate about these deleterious practices in the academic context. Originality/value: the paper highlights evidence of dishonest behavior in the academy, which is sometimes overlooked by several stricto sensu management postgraduate programs.